Impact of Smartphones Addiction upon Primary School Pupil's Achievements at Al-Rusafa Educational Directorate in Baghdad City - Jalil, Marwa; Jabbar, Wissam (Iraqi National Journal of Nursing Specialties, 2020)
Objectives: To determine Smartphone addiction among primary school students and its impacts. The samples of the study were240primary school students in derived from stratified random sampling. The questionnaire was used to collect the data. The data were then an- analyzed using correlation statistics. It also caused a negative impact on demic performance of the primary school students.Methodology: A cross- sectional study in assessment approach in applied in order to achieve the earlier stated objectives. The study was initiated from October 1st, 2019 to April 30th, 2020. Simple random sampling (probability) sample of (240) Pupils study In primary school at Al-Rusafa first directorate schools in Baghdad City.Results: The study results show that the longer the duration of using smartphone, the worse the health and behavioral aspects as perceived by. The longer the average of daily smartphone use, the poorer the school achievement. The longer the average of daily use of social media texts and each of adverse effects of smartphone use, the better the health and behavioral aspects as perceived by parents.Recommendations: The study recommends that there is a need for community health nurses to initiate health education activities that aim to increase public’s awareness about the adverse effects of using smartphone by children. There is a need to devote more efforts to increase parents’ awareness; particularly those who are young and with low educational levels, about the adverse effects of using smartphone by children and never allowing their children to own their smartphone.